The first Sterling Area†. (4th May 2016) - Allen, Martin
Abstract : Between the eleventh century and mid‐thirteenth century a Sterling Area evolved in the British Isles, with a common currency based upon the English silver penny and equivalents of it produced in Scotland and Ireland. This Sterling Area began to contract in the second half of the fourteenth century, when reductions in the bullion content of Scottish coins ended the equivalence of the English and Scottish currencies, and in the fifteenth century Ireland developed its own coinage. Estimates of the currency of the Sterling Area are provided, taking the chronology of its growth and contraction into account. Estimates of the sterling currency are not estimates of the currency of England, and they cannot be combined with data relating exclusively to England in economic modelling, without qualification. Per capita currency estimates and values of coin hoards and single coin finds are at a high level around 1400, falling in the second half of the fifteenth century, indicating that the European 'bullion famine' of the 1390s to c . 1415 had less effect on the currency than the second late medieval bullion crisis, from the 1430s to the 1460s.